A fortunate presentation of intestinal obstruction secondary to a rare sarcomatoid tumour of the small bowel - Rawther, Thampi; O’Brien, Sean; Das, Kamala K. (International Surgery Journal, 2023)
Intussusception in the adult is rarely from a benign cause and is almost always pathological. Causes include carcinomas, polyps, Meckel’s diverticulum, or colonic diverticulum. Common symptoms include abdominal pain, intestinal obstruction, palpable abdominal mass, gastrointestinal (GI) bleeding, and anaemia. Sarcomatoid carcinoma is a rare type of small intestinal malignancy exhibiting carcinomatous and sarcomatous features. It primarily affects older patients, mean age 57, and is 1.5 times more prevalent in men. This is an interesting case report of a patient presenting with intussusception secondary to a sarcomatoid tumour of the small bowel. Surgery is the treatment of choice in adults with intussusception due to the high malignancy potential. Furthermore, surgical resection of the affected bowel is the definitive form of therapy as small bowel sarcomatoid tumours are not responsive to chemotherapy and radiotherapy. Early surgical intervention helps reduce mortality as it allows for early staging, treatment, and monitoring of the tumour. The patient was fortunate to have presented with intussusception, facilitating early surgical intervention, and was found to have a low disease stage.